X-ray system simulation software tools for radiology and radiography education. (1st February 2018) - Kengyelics, Stephen M.; Treadgold, Laura A.; Davies, Andrew G.
Abstract: Objectives: To develop x-ray simulation software tools to support delivery of radiological science education for a range of learning environments and audiences including individual study, lectures, and tutorials. Methods: Two software tools were developed; one simulated x-ray production for a simple two dimensional radiographic system geometry comprising an x-ray source, beam filter, test object and detector. The other simulated the acquisition and display of two dimensional radiographic images of complex three dimensional objects using a ray casting algorithm through three dimensional mesh objects. Both tools were intended to be simple to use, produce results accurate enough to be useful for educational purposes, and have an acceptable simulation time on modest computer hardware. The radiographic factors and acquisition geometry could be altered in both tools via their graphical user interfaces. A comparison of radiographic contrast measurements of the simulators to a real system was performed. Results: The contrast output of the simulators had excellent agreement with measured results. The software simulators were deployed to 120 computers on campus. Conclusions: The software tools developed are easy-to-use, clearly demonstrate important x-ray physics and imaging principles, are accessible within a standard University setting and could be used to enhance the teaching of x-ray physics to undergraduate students. Advances in knowledge: Current approaches to teaching x-ray physics in radiological science lack immediacy when linking theory with practice. This method of delivery allows students to engage with the subject in an experiential learning environment.